Praktik Nominee dalam Pranata Hukum Perseroan Terbatas di Indonesia (Analisis Sinkronisasi Undang-Undang Perseroan Terbatas, Undang-Undang Penanaman Modal, dan Undang-Undang Tindak Pidana Pencucian Uang) - Mutia Ramadina; Pieter E. Latumeten (UNES Law Review, 2023)
Development in Indonesia emphasizes the need for funds for productive projects, including foreign investments. However, limitations on share ownership have led to the practice of nominees in limited liability companies. This research analyzes the validity of nominee agreements and the synchronization of relevant regulations in Indonesia. The research method employed is descriptive analytics with a normative juridical approach. The findings indicate that the nominee practice, despite its common use, may violate regulations, particularly prohibitions on agreements declaring share ownership on behalf of others. In conclusion, this research highlights the complexity and challenges of regulating nominee practices within the existing regulatory framework in Indonesia.